157k views
0 votes
If f(x)= x-6 and g(x)=x^1/2(x+3), find g(x)xf(x)

User Ejoubaud
by
5.7k points

1 Answer

3 votes

Answer:


f(x)= x-6\\g(x) = x^(1)/(2) (x+3)\\\left(x-6\right)\left(x^{(1)/(2)}\left(x+3\right)\right):\quad x^{(5)/(2)}-3x^{(3)/(2)}-18x^{(1)/(2)}\\x^2√(x)-3x√(x)-18x^{(1)/(2)}\\

Factor and you get


x^(1)/(2) (x-6)(x+3)

Hope this helps!!!

User Luis Aguilar
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.